Poland Syndrome- A Rare Congenital Condition - Hossain, Homayra Tahseen; Khandaker, Md Abul Kashem; Islam, Quazi Tarikul; Ahasan, HAM Nazmul; Adnan, Munshi MB Md Shoaib; Islam, Nazmul (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Named after Sir Alfred Poland, Poland syndrome is a rare congenital anomaly classically characterized by the absence of unilateral chest wall muscles and sometimes ipsilateral symbrachydactyly (abnormally short and webbed fingers). The aetiology is probably a vascular disruption sequence of the subclavian arteries. In most cases, Poland Syndrome is sporadic. We report a 26 year old male patient with typical features of Poland Syndrome associated with bronchiectasis and mitral valve prolapse- a very rare association. To the best of our knowledge, this is the first documented case of a Poland Syndrome with rare association reported from Bangladesh. J Bangladesh Coll Phys Surg 2018; 36(4): 166-169